PROBLEMS AND PRIORITIES OF INVESTMENT AND INNOVATIVE DEVELOPMENT OF THE REGION’S INDUSTRIAL SECTOR - KATKOVA, Tetiana; MELNYCHENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the study, the focus of the scientific discourse is on the aspects of identifying problems and obstacles, as well as the justification of management decisions in the field of public policy to ensure the development of the industrial sector of the regional economy. It was established that industrial enterprises belong to the real sector of the regional economy, therefore, they need to ensure their competitiveness on the basis of innovation and technology. At the same time, innovative and technological development of business entities in the industrial sector requires significant investments. Therefore, the perspective and relevance of the innovation-technological path (vector) and the type of development of the industrial sector of the regional economy have been proven. Therefore, the purpose of the research is to generalize the problematic aspects, as well as to substantiate the priorities of the regional policy of investment and innovation development of the industrial sector of the regional economic system. For these purposes, a set of measures focused on the development of the regional institutional infrastructure of investment and innovation support for the development and strengthening of the competitive positions of the industrial sector of the region is proposed. The scientific novelty of the research results lies in the determination of the directions, mechanisms and means of improving the institutional-legal, institutional-organizational and infrastructural components of the improvement of the regional institutional infrastructure, the support of investment and innovation activities and the development of subjects of the industrial sector of the regional economic system. The practical significance of the research results lies in the determination of a system of measures and means that are available to regional authorities and at the same time effective from the point of view of ensuring the investment and innovation development of the industrial sector of the region.